2014
DOI: 10.36076/ppj.2014/17/315
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Metastatic Spinal Lesions with a Navigational Bipolar Radiofrequency Ablation Device: A Multicenter Retrospective Study

Abstract: Background: Spinal metastatic lesions are a common occurrence among oncology patients and contribute to significant morbidity. Treatment options have been limited in their effectiveness and scope to this point. Objective: This study aims to report the safety and efficacy of radiofrequency ablation (RFA) of malignant spinal lesions using a novel RFA bipolar tumor ablation system which includes a navigational electrode containing 2 active thermocouples. Study Design: IRB approved multicenter retrospective review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…A total of 25 nonrandomized studies (21 retrospective, 4 prospective) published between 2008 and 2022 were included based on the inclusion/exclusion criteria (Supplementary Fig. 1) [5] , [15] , [16] , [17] , [19] , [20] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] . All included studies reported exclusively on metastatic spinal tumors.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 25 nonrandomized studies (21 retrospective, 4 prospective) published between 2008 and 2022 were included based on the inclusion/exclusion criteria (Supplementary Fig. 1) [5] , [15] , [16] , [17] , [19] , [20] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] . All included studies reported exclusively on metastatic spinal tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Other musculoskeletal ablation studies had higher rates of previous radiation use or did not report the numbers [ 7 9 , 32 ]. Goetz reported 74% of patients were treated with radiation [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…[25] 6.7 (±1.7) 3.2 (±1.4) P < .001 24 h 100% 1.4 (±1.3) P < .001 4 wk 1.1 (±0.8) P < .001 12 wk 1.0 (±0.7) P < .001 24 wk Chen et al [27] 6 (NA) 5 (NA) P < .05 3 d 86% 3 (NA) P < .05 1 mo 92% 3 (NA) P < .05 3 mo 92% 3 (NA) P < .05 6 mo 89% Zhang et al [28] 6.4 (±2. [30] 7.8 (±1.1) 3.5 (±2.0) P < .01 24 h NA Anchala et al [31] 7.51 (±2.46) 1.71 (±2.28) P < .0001 1 wk 54% 2.25 (±2.44) P < .0001 1 mo 1.75 (±2.62) P = .009 6 mo Zheng et al [32] 7.69 (±1.12) 6.62 (±1.02) P < .01 3 d NA 3.62 (±0.98) P < .01 1 mo NA 2.77 (±0.82) P < .01 3 mo NA Abdelgawaad et al [33] 7.2 (±2.3) 2.7 (±1.09) P = .0001 3 d NA 3 (±2.1) P = .0001 6 mo 83.3% Lv et al [34] 7. 52 [35] 8.…”
Section: Subgroup Analysismentioning
confidence: 93%
“…Three of the studies reported that no complications occurred in their cohorts. [24,31,32] Overall, the rest of the studies reported that 27.4% (n = 139) of patients receiving MWA reported complications, while 10.9% (n = 23) of patients receiving RFA had complications. MWA alone or in combination with surgery for spinal metastases has more major complications, including nervous system complications such as nerve injury, nerve function defect, persistent pain, pathological fracture, etc.…”
Section: Postoperative Complicationsmentioning
confidence: 99%
See 1 more Smart Citation